The Concept of Children's Faith Education (Comparative Study Abdullah Nashih Ulwan and Zakiah Daradjat Thoughts) - Rezka, Aulia Gita; Subandi, Subandi; Amiruddin, Amiruddin (Bulletin of Science Education, 2024)
The article aims to describe the children's faith education on comparison of Abdullah Nashih Ulwan and Zakiah Daradjat Thoughts. The research methodology applied in this study is literature review, also known as library research. Primary data sources consist of works by Abdullah Nashih Ulwan, such as "Tarbiyatul Aulad Fil Islam: Pendidikan Anak Dalam Islam," and works by Zakiah Daradjat, such as "Islam dan Kesehatan Mental," "Ilmu Jiwa Agama," "Pendidikan Islam dalam Keluarga dan Sekolah," and "Ilmu Pendidikan Islam." Secondary data sources involve other relevant books on the topic. The data analysis method employed is content analysis. From the author's research, the thoughts of Abdullah Nashih Ulwan and Zakiah Daradjat on faith education encompass both content and methods. There is a similarity in the thoughts of these two figures, specifically in terms of the content of faith education, the use of the concept of tawhid to guide children's lives, instilling worship habits, educating children about muraqabatullah, and employing exemplary and habituation methods. At the same time, there are differences in the use of punishment in education; Abdullah Nashih Ulwan allows punishment but focuses on methods taught by Islam, while Zakiah Darajat does not use punitive education in child upbringing. Keywords: Children's Faith Education, Abdullah Nashih Ulwan Thoughts, Zakiah Daradjat Thoughts